Experimental study of gas flow and coal deformation at different levels of axial/radial stress ratio - Hang Long; Hai-fei Lin; Dong-min Ma; Chen Chen; Shu-gang Li; Yang Bai (Scientific Reports)
CH4 flow dynamics in coal, governed primarily by adsorption, desorption, and seepage processes, are critical for determining gas extraction efficiency. Coal seam deformation under varying stress conditions further significantly impacts CH4 flow. Utilizing a self-developed coal solid-gas coupling test apparatus, this study conducted simultaneous measurements of CH4 flow and coal deformation under different axial-to-radial stress ratios. The temporal relationship between CH4 flow and coal deformation was analyzed, establishing a quantitative correlation between the two. The influence of stress on both phenomena was examined. A model incorporating residual strain was developed to evaluate coal strain throughout the entire CH4 flow process. Results demonstrated that both CH4 flow and coal deformation exhibit Langmuir-like relationships with time. Similarly, a Langmuir-like relationship was observed between the amount of CH4 adsorbed and coal deformation during adsorption. Within the experimental stress range, an increase in the axial-to-radial stress ratio inhibited CH4 flow, consequently reducing coal deformation. Volumetric strain exhibited greater sensitivity to changes in the stress ratio compared to radial or axial strain. Residual strain was identified in coal during both CH4 adsorption and desorption, with its prominence inversely related to the axial-to-radial stress ratio. The model, accounting for residual strain alongside isothermal flow and deformation characteristics, accurately represented the temporal evolution of coal deformation during CH4 flow. This research provides a theoretical foundation for enhancing the efficacy of gas extraction.